The Influence of Leadership Style, Work Environment and Organizational Commitment on State Civil Apparatus Performance - Muh. Yusuf Q.; Muhammad Aqsa; Charlie Charlie (Kontigensi : Jurnal Ilmiah Manajemen, 2020)
The organization's success in achieving its goals is dependent on how good the quality of the performance of its employees is. In this study, performance is used as an independent variable and leadership style, work environment, and organizational commitment as dependent variables. In this study, there were 100 samples used with data testing tool using SPSS 21. The results are that leadership style, work environment, and organizational commitment have a positive and significant influence on the performance of ASN at the Agriculture Service, Fisheries Service, Food Security Service, and Land Office of Palopo City simultaneously and partially where all the significance value is below the alpha level.